Differences in risk factors for partial and no immunisation in the first year of life: prospective cohort study. Issue 7553 (1st June 2006) - Samad, Lamiya; Tate, A Rosemary; Dezateux, Carol; Peckham, Catherine; Butler, Neville; Bedford, Helen
Abstract: Objective To compare demographic, social, maternal, and infant related factors associated with partial immunisation and no immunisation in the first year of life in the United Kingdom. Design Prospective cohort study. Setting Sample of electoral wards in England, Wales, Scotland, and Northern Ireland, stratified by measures of ethnic composition and social disadvantage. Participants 18 488 infants born between September 2000 and January 2002, resident in the UK and eligible to receive child benefit (a universal benefit available to all families) at age 9 months. Main outcome measure Immunisation status at 9 months of age, defined as fully immunised, partially immunised, or not immunised. Results Overall in the UK, 3.3% of infants were partially immunised and 1.1% were unimmunised; these rates were highest in England (3.6% and 1.3%, respectively; P < 0.01). Residence in ethnic or disadvantaged wards, larger family size, lone or teenaged parenthood, maternal smoking in pregnancy, and admission to hospital by 9 months of age were independently associated with partial immunisation status. In contrast, a higher proportion of mothers of unimmunised infants were educated to degree level or above (1.9%), were older (3.1%), or were of black Caribbean ethnicity (4.7%). Conclusions Mothers of unimmunised infants differ in terms of age and education from those of partially immunised infants. Interventions to reduce incomplete immunisation in infancy need different approaches.